THE CORRELATION NOUN PHRASE AND WRITING OF DESCRIPTIVE TEXT AT TENTH LEVEL STUDENTS OF SMA N 5 OKU - Mila Arizah; Tri Molly Ramadhona (BASIS (Bahasa dan Sastra Inggris), 2019)
The aim of this research was to find out whether or not there was a significant correlation between noun phrase and writing descriptive text. This study was using quantitative approach. The technique for collecting data was noun phrase test and written test. This study was conducted at SMA N 5 OKU. The population of this study was the tenth grade students of SMA N 5 OKU in academic year 2018/2019 and the samples were 122 students which were choosen randomly from the population. The data were collected by using noun phrase test and written test. The data were analyzed by using the correlational analyses and computerized by using SPSS 23. After conducting the research, the researcher got the data which showed that there was significant correlation between noun phrase and writing descriptive text. The correlation was significant in terms of the correlation coefficient was 0.424. It meant that research hypothesis (Ha) alternative hypothesis was accepted and (Ho) null hypothesis was rejected.